Civil Proceedings During Quarantine - TATULYCH, Iryna Yuriyivna (European Journal of Law and Public Administration, 2020)
In the mechanism of protection of rights, freedoms, interests of a person, as well as interests of the state and society, the judicial form of protection is the most effective and perfect one. However, in connection with the Coronavirus disease pandemic on March 11, 2020, the Cabinet of Ministers of Ukraine set up the quarantine by Resolution № 211. On Prevention of the Spread of Coronavirus COVID-19 in Ukraine, and for this period there was introduced a special regime in Ukrainian courts. As a result, the judicial system faces the question: “How to simultaneously ensure the right of citizens to effective judicial protection under Art. 55 of the Constitution of Ukraine, Art. 4 of the Civil Procedural Code (hereinafter referred to as the CPC of Ukraine), other national legislation and protect the population from such an acute infectious disease?” Due to the significant spread of COVID-19 and setting up the quarantine throughout Ukraine on March 12, special attention needs to be paid to the organization of the continuous operation of courts to dispense justice and ensure the constitutional right of citizens to fair judicial protection. And the most important thing in such conditions is to ensure continuous and safe access of citizens to justice, especially in the courts of the first instance, because citizens apply to them, first of all, and judges of local courts are the first to protect human rights and freedoms.
Keywords: proceedings, justice, participate, Electronic Court, quarantine.